Molecular defects in the beta-globin gene identified in different ethnic groups/populations during prenatal diagnosis for beta-thalassemia: a Malaysian experience - Tan, J.; George, E.; Tan, K.L.; Chow, T.; Tan, P.C.; Hassan, J.; Chia, P.; Subramanium, R.; Chandran, R.; Yap, S.F. (2004)
beta- thalassemia is the most-common genetic disorder of hemoglobin synthesis in Malaysia, and about 4.5 of the population are heterozygous carriers of the disorder. Prenatal diagnosis was performed for 96 couples using the Amplification Refractory Mutation System and Gap-Polymerase Chain Reaction. We identified 17 beta-globin defects-initiation codon for translation (T-G), - 29 (A-G), 28 (A-G), CAP + 1 (A-C), CD 8/9 (+ G), CD 15 (G-A), CD 17 (A-T), CD 19 (A-G), Hb E (G-A), IVS1-1 (G-T), IVS1-5 (G-C), CD 41/42 (- CTTT), CD 71 - 72 (+ A), IVS2-654 (C-T), poly A(A-G), 100-kb (G)gamma((A)gammadeltabeta)degrees and 45-kb Filipino deletions. The 192 beta-alleles studied comprised Chinese (151 patients), Malay (21), Orang Asli from East Malaysia (15), Filipino ( 1), Indian ( 1), Indonesian Chinese ( 2), and Thai (1). In the Chinese, 2 beta-globin defects at CD 41/42 and IVS2-654 were responsible for 74 of beta-thalassemia. beta-mutations at CD 19, IVS1-1 (G- T), IVS1-5, poly A, and hemoglobin E caused 76 of the hemoglobin disorders in the Malays. The Filipino 45-kb deletion caused 73.3 of b-thalassemia in the Orang Asli. Using genomic sequencing, the rare Chinese beta-mutation at CD 43 (G-T) was confirmed in 2 Chinese, and the Mediterranean mutation IVS1-1 ( G- A) was observed in a Malay beta-thalassemia carrier. The beta-globin mutations confirmed in this prenatal diagnosis study were heterogenous and 65 (68) couples showed a different globin defect from each other. The use of specific molecular protocols has allowed rapid and successful prenatal diagnosis of beta-thalassemia in Malaysia.